Synergistic Effect of Arecoline in Combination with Doxorubicin on HeLa Cervical Cancer Cells - Astrid Ayu Maruti; Fikri Amalia; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2015)
Arecoline, the main alcaloid of Areca cathecu L has been proven to posses cytotoxic activity against various cancer cell lines. The research conducted to examine the cytotoxic activity of arecoline alone and its combination with doxorubicin against HeLa cervical cancer cell line. Single treatment of arecoline in various concentration on HeLa cancer cell were done followed by the combinational treatment with doxorubicin. The cell viability as the parameter of cytotoxicity was measured using MTT (3-(4,5-dimetiltiazol-2-il)-2,5-difeniltetrazolium bromide) assay. The apoptotic effect was examined by double staining assay using etidium bromide–acridin orange.  Arecoline did not show potent cytotoxicity effect against HeLa since the value of IC50 is 462 µM. The combinational treatment of arecoline and doxorubicin showed synergicity with the optimum CI value is 0,48 given by the treatment of 30mM arecoline combined with 125 nM doxorubicin. The result of this study shows that arecoline has potential to be proposed as co-chemotherapeutic agent for cervical cancer. However, further study on its molecular mechanism needs to be conducted. Keywords:  cinnamon essential oil, doxorubicin, T47D cells, combination cytotoxicity